RGB color image watermarking using Discrete Wavelet Transform DWT technique and 4-bits plan by histogram stretching - Kadhim, Karrar Abdul Ameer (2013)
Recently, access to multimedia data has become much easier due to rapid growth of the internet; everyone could access these data, and use them for personal or commercial purposes, for these reason copy right problems appeared. Digital watermarking techniques are used to protect the copyrights of multimedia data by embedding secret information in the host media, for example, embedding in images, audios, or videos. Many watermarking techniques have been proposed in the literature to solve the copyright violation problems, but most of these techniques failed to satisfy both imperceptibility and robustness requirements. In this thesis, adaptive color image watermarking technique is proposed. The proposed technique involves two main stages, which are, embedding, and extraction. Before embedding stage, a host image is converted from RGB to YCbCr color space to preserve imperceptibility and robustness, then, Cb component is extracted and partitioned into four quadrants. In the embedding stage select Cb component to apply DWT to decompose the cover image to four frequencies which are LL, HL, LH and HH, then selected the LH2 band to embedding the watermark image, while watermark image will convert to 4-bits plane to compress the image to ensure the capacity. In the extracting stage, DWT is used again to decompose the selected quadrant of watermarked image, and finally the watermark image is extracted. To prove the efficiency of proposed technique, six types of attacks are applied on watermarked image namely, Gaussian noise, Salt & Pepper Noise, Sharpening filter, Median filter, Rotation, and JPEG Compression. The experiments results have shown that the proposed technique successfully withstood against all the mentioned attacks, and at the same time preserved the watermarked image quality.